The efficiency of chemo-radiotherapy for localized recurrence of esophageal cancer after radical esophagectomy - Asaumi, Yoshihide; Miyanaga, Tamon; Nishida, Yoji; Hashizume, Yasuo; Tamamura, Hiroyasu (European Journal of Oncology and Environmental Health, 2015)
Background: Radiation therapy for postoperative loco regional recurrence of esophageal cancer has been reported to be effective. The purpose of the present study was to evaluate the usefulness of radiotherapy combined with standard dose 5-fluorouracil (5FU) and cisplatin for the treatment of postoperative loco regional recurrent esophageal cancer. Method: Between 2004 and 2010, 10 patients with postoperative recurrence of esophageal cancer received concurrent chemoradiotherapy (CRT) using 5-FU and cisplatin. We evaluated the response rate, overall survival, and any adverse events. Results: Nine out of 10 patients had mediastinal lymph node recurrence, and 1 patient had a cervical lymph node recurrence. Nine patients were irradiated with 58-64Gy, and 1 patient could not complete CRT due to mediastinitis at 34Gy. Complete response (CR) was recognized in 4 patients (40%), and partial response (PR) in 4 patients (40%). The overall median survival time was 13 months. The histological type was a well-differentiated squamous cell carcinoma in 3 of the 4 patients where CR was obtained. CRT was discontinued with 1 patient who experienced a tracheomediastinal fistula. Because of hemorrhage due to radiation gastritis, transfusion of red cell concentrates was required. Steroids were required to treat intermittent pneumonitis. Conclusion: Chemoradiotherapy using 5-FU and cisplatin for loco regional postoperative recurrence of esophageal cancer was an effective therapy for well-differentiated squamous cell esophageal cancer, but one must beware of severe adverse events.